Interrelationship of identity and ecology : mapping the journey as a means of knowing - Litaker, Alexandra Kathleen, 1970- (2012)
Í lokaverkefni mínu í meistaranámi í listkennslufræði rannsakaði ég tengingu einstaklingsins, samfélagsins og náttúrulegs umhverfis með kennslu og listrannsókn Kennslan var 6 vikna námskeið fyrir konur með MS sjúkdómin og var það sambland af dansi, hreyfiþekkingu, mæltu máli og listsköpun. Námskeiðið var haldið í MS setrinu 2011. Á sama tíma og á eftir námskeiðinu gerði ég listrannsókn sem endaði með sýningunni Bláa fjallið þitt í Íslensk grafík í september 2012. Þar fékk ég innblástur frá feminísku skáldsögunni The Golden Notebook eftir Doris Lessing (1962). Í meistararitgerðinni tala ég um þann útgangspunkt ásamt lesefni sem tengist flökkuborgurum, stjórnmálum staðar, lestur sem virk merkingar upptaka, samræðum og sagnarformið notað sem kennslutæki í listsköpun. Einnig fjalla ég um í ritgerðinni hvernig þessi hugtök tengjast sýningu minni og námskeiði fyrir konur með MS. As a woman with foreign roots living in Iceland I found myself confronted with questions of national and social identity and the ways in which one negotiates and experiences place as both natural and social phenomena. For my thesis projects I proposed to investigate the interplay of concepts of self and ecology through the creation of both a workshop and an artistic research project. Inspired by the classic feminist novel of identity The Golden Notebook by Doris Lessing (1962), I began a series of notebooks and mappings as research that culminated in a workshop combining somatics, dance, and art for women who have Multiple Sclerosis and in an art exhibition held the summer of 2012 entitled Your Blue Mountain at the gallery of the Icelandic Printmakers Association. This thesis examines theoretical readings that explore concepts of nomadic identity, politics of place, reading as active meaning making, and dialogue and storytelling as pedagogy in art. In this thesis I reflect on the ways the MS workshop and my artistic research that culminated in the exhibition Your Blue Mountain engage with these readings.